SHARIA BANKING FINANCING INSTRUMENTS IN THE FORM OF DEBT FINANCING - Asrat Nita Waty; Muhammad Yadi Harahap (PT. Radja Intercontinental Publishing, 2023)
Instruments in sharia banking have many forms of contracts or financing that are used in sharia banking. Even though you have many contracts or types of financing, sharia banking must be based on sharia principles. Legally, sharia banking is regulated in Law Number 21 of 2008 concerning sharia banking. However, sharia banking must also refer to the Koran and hadith which are contained in the DSN-MUI fatwa. Murabahah contracts are used in sales and purchase principle products, contracts or sales and purchase agreements can technically be applied in the banking world, especially sharia banking. Murabahah financing almost dominates all forms of distribution of funds to sharia banks, in number, this gives the impression that all sharia bank fund distribution transactions are deliberately made murabahah, possibly to minimize the risks that will befall the bank in each distribution of funds. By utilizing the concept of a sale and purchase agreement, transactions in banking can be avoided from usury. Compared to other financing mechanisms, murabahah is the most profitable and carries the least risk for sharia banks.